Logistics and Supply Chain Management / Strategies for Reducing Costs and Improving Services - Christopher Martin (Pitman Publishing, 1992)
Logistics and Competitive Strategy, The Customer Service Dimension, Measuring Logistics Costs and Performance, Benchmarking the Supply Chain, Managing the Global Pipeline, Strategic Lead-Time Management, Just-in-Time and Quick Response Logistics, Managing the Supply Chain, Leading-Edge Logistics, Index.
Logistics and Competitive Strategy, The Customer Service Dimension, Measuring Logistics Costs and Performance, Benchmarking the Supply Chain, Managing the Global Pipeline, Strategic Lead-Time Management, Just-in-Time and Quick Response Logistics, Managing the Supply Chain, Leading-Edge Logistics, Index.